A Model for Humanitarian Supply Chain: An Operation Research Approach. (2018) - Gutierrez, Ma.Teodora E.; Mutuc, Jose Edgar S.
Abstract: The study presents a mathematical model for identification of the optimum location of a temporary or fixed facility in a certain geographic area being studied. Particularly, it is applied to Humanitarian Supply Chain where it seeks to identify the best location of temporary relief center operations in order to optimize the delivery of relief goods to the randomly dispersed evacuation centers. The paper seeks to optimize the movement of relief goods by minimizing the total transportation cost using Operation Research approach with the integration of Center of Gravity method. The center of gravity approach aims to locate a facility where it reflects equality of distances and demand volume in a network of customers' locations. A case study was applied to use the model. The results revealed the geographic coordinates of the optimum location of the facility. The identified optimum location will have a total savings of 40% in the total transportation cost. Hence, by a significant reduction of the transportation cost will also mean a significant reduction of response time and delivery time of relief goods because these transportation cost are functions of distances of customers location and a function of volume of customers' demand. The identified optimum facility location could also be a prepositioned location of relief goods covering the affected areas in the city. The proposed model for disaster facility location is easy to use and require simple tasks to implement. The model is readily accessible to managers and planners so it can be used in their planning.